PENGARUH PROFESIONALISME GURU AGAMA TERHADAP PENDIDIKAN KARAKTER SISWA SEKOLAH DASAR ISLAM - Kurniawan, Diki (Idaarah: Jurnal Manajemen Pendidikan, 2017)
This study aims to determine the influence of professionalism of religious teachers on the character education of students at SDIT Mitra Cendekia Indonesia Setu Tangerang Selatan, Banten. SDIT grade VI students totaling 30 people are the subject of research. This research uses two kinds of variables namely 1) free variable: professionalism of religious teachers , 2). Student character education. Data retrievel is obtained by using questionnaire with likers scale. The data analysis technique used is descriptive analysis to calculate the mean, median, standard deviation. As for hypothesis using simple linear regression analysis and coefficient of determination to know percentage of professionalism teachers adherent to the character education of students. The results of research indicate that there is a positive and sufficient influence between teachers professionalism to character aducation. I can be see from the t count > t table ( 2,948 > 2,04).